2021
DOI: 10.1038/s41467-021-25090-9
|View full text |Cite
|
Sign up to set email alerts
|

Dpb4 promotes resection of DNA double-strand breaks and checkpoint activation by acting in two different protein complexes

Abstract: Budding yeast Dpb4 (POLE3/CHRAC17 in mammals) is a highly conserved histone fold protein that is shared by two protein complexes: the chromatin remodeler ISW2/hCHRAC and the DNA polymerase ε (Pol ε) holoenzyme. In Saccharomyces cerevisiae, Dpb4 forms histone-like dimers with Dls1 in the ISW2 complex and with Dpb3 in the Pol ε complex. Here, we show that Dpb4 plays two functions in sensing and processing DNA double-strand breaks (DSBs). Dpb4 promotes histone removal and DSB resection by interacting with Dls1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…In this study, we focused on the MMS resistance. Dpb3 and Dpb4, the two nonessential subunits of the polymerase ε holoenzyme, fold together and form a heterodimer ( Tsubota et al 2006 ), while Dpb4 has functions also in the context of the ISW2/yCHRAC complex ( Iida and Araki 2004 ; Casari et al 2021 ). We found that single DPB3 or DPB4 deletions caused the same phenotype as loss of both Dpb3 and Dpb4 regarding their effect on ctf4 Δ’s sensitivity to MMS ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we focused on the MMS resistance. Dpb3 and Dpb4, the two nonessential subunits of the polymerase ε holoenzyme, fold together and form a heterodimer ( Tsubota et al 2006 ), while Dpb4 has functions also in the context of the ISW2/yCHRAC complex ( Iida and Araki 2004 ; Casari et al 2021 ). We found that single DPB3 or DPB4 deletions caused the same phenotype as loss of both Dpb3 and Dpb4 regarding their effect on ctf4 Δ’s sensitivity to MMS ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The density of nucleosome packaging is regulated by ATP-dependent chromatin remodelers, which use the energy derived from ATP hydrolysis to evict, assemble, reposition or exchange histones throughout the genome. We have previously shown that the lack of the chromatin remodeler Isw2 dramatically impairs nucleosome disassembly at DSBs ( 103 ), prompting us to test the effect of its deletion on sae2 Δ suppression, Ku association with DSBs, and DSB tethering. The lack of Isw2, which impaired H2A and H3 removal from the HO-induced DSB (Figure 7D ), partially suppressed both the DNA damage sensitivity (Figure 7E ) and the end-tethering defect of sae2 Δ cells (Figure 7A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…4H). It has been reported that POLE3 promotes checkpoint activation, and loss of POLE3 enhances cells’ sensitivity to ATR inhibitor, poly(adenosine 5′-diphosphate–ribose) polymerase (PARP) inhibitor, and CPT ( 33 35 ). Together, these results indicate that POLE3 is a potential target of WDR70, implying that POLE3 is probably involved in genomic integrity maintenance by WDR70.…”
Section: Resultsmentioning
confidence: 99%
“…One of functions is that promoting histone removal and DSB resection by interacting with histone fold protein Dls1. The other is to promote checkpoint activation by interacting with Dpb3 ( 35 ). To assess the possible role of POLE3 in CHRAC complex during DSBs repair, we first used coimmunoprecipitation and fluorescence resonance energy transfer (FRET) assay to investigate the interaction with the subunits of CHRAC complex.…”
Section: Resultsmentioning
confidence: 99%